Respuesta :

Hello from MrBillDoesMath!

Answer:

Top line: y = (2/3)x + 2

Bottom line:  y = (2/3)x  -1

Discussion:

The graph provided is hard to read but I did the best I could.

The top line appears to pass through the points (0,2) and (-3,0)

For this line

m =  change y /change x = (0-2)/(-3-0) = -2/-3 = +2/3. So

y = mx + b => y = (2/3) x+ b.  As the line passes through (0,2) set x = 0, y= 2 in y = (2/3)x + b =>  

2 = (2/3) 0 + b   => b = 2

Therefore    y = (2/3)x + 2

The bottom line appears to pass through the points (0,-1) and (3,1)

For this line

m =  change y /change x = (1-(-1)) /(3-0) = +2/-3. So

y = mx + b => y = (2/3) x+ b.  As the line passes through (0,-1) set x = 0, y= -1  in y = (2/3)x + b =>  

-1  = (2/3) 0 + b   => b = -1

Therefore    y = (2/3)x + -1

Thank you,

MrB